Migrant Memory, Movement, and Misrecognition: Reactivating Diasporic Experience Toward an Anticolonial Politics of Place - Ortuzar, Jimena (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2021)
How might diasporic experiences of loss and displacement aid immigrants in responding to and acknowledging Indigenous lands and territories? Drawing from my own immigrant experience, I retrace and reinvent my movement in Tkaronto through walking practices that recover memories of migrancy as a newcomer to the land known as Canada. Such memories can be useful sources for immigrants to consider their relationship to settler colonialism. Reactivating them through movement might elicit a new responsiveness to the land as well as recognition of its caretakers and their struggles. I reflect on the possibilities that such a practice of walking and thinking through embodied memories can open up for undoing the coloniality of thought that underpins migrant aspirations for “a better-than-survival kind of living” (Berlant) and that so often results in assimilation to, and participation in, a settler colonial state.